Hemorragia Post – Parto en el Hospital de Apoyo Integrado Tarapoto, 1992 - Rengifo Ríos, Catalina (1992)
Was performed at the Hospital of Integrated Support Tarapoto descriptive, longitudinal, prospective, analytical study to determine the frequency of postpartum hemorrhage associated factors, causes and determine the average volume impacts hemodynamics of the mother. They took full term pregnant women, excluding patients with medical and obstetric complications. 399 cases were recorded, with an average volume of blood loss was 543.45 cc., Found 44.1% of cases with post-partum hemorrhage, the volume of 1259.23 cc., Which impact on the hemodynamics of the patient. The associated risk factors were prolonged labor, time delivery and fetal weight. The causes of bleeding were associated with dissociated membranes (44.74%), lethargy / hypotonia uterine (28.95%), retained placenta (18.42%), cervical laceration (5.26%) and third degree laceration (2.63%). Finally, the linear correlation analysis shows an inverse relationship with post-duck hematocrit, systolic and diastolic blood pressure and a direct relationship to heart rate.